Hubungan Penerapan Pola Pendidikan Kristen dalam Keluarga terhadap Perkembangan Karakter Remaja di SMP Elpida Kelas VII Tahun Ajaran 2021/2022 - Daeng Salfina Dethan; Petrus Kefas Loka; Elisabeth Dethan (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Christian education plays a very important role and is the main basis in the family to educate and develop children's character into individuals who fear God (Proverbs 1:7). Character is a way of thinking and behaving that is characteristic of each individual to live together, both within the family and society. Individuals with good character are individuals who can make decisions and are ready to be responsible for every consequence of the decisions they make. For this reason, the Christian education pattern is very important to be a foothold in training children's character. Specifically, the Christian education pattern is one of the education patterns that teaches the Word of God so that children have guidelines in their lives and ultimately they experience changes in terms of character, behavior and actions. There are various forms of education patterns used by parents in educating children. Among them are 3 forms of education patterns discussed in this thesis, namely authoritarian, democratic and Laisses Faire education patterns. Where this education pattern is used by parents to shape the character of children, but without Christian education, the character of children will remain rotten. For families, they must provide Christian education from an early age to their children so that their character is formed well. Because the family is the main institution in educating children, the most successful child education is if parents walk according to the standards set by God. For Christian parents, the result of education is that our children have respect for God, for us as parents, for the church, and for the country.